The role of ferroptosis in colorectal cancer and its potential synergy with immunotherapy - Xia, Wenhua; Lv, Yuanhao; Zou, Yan; Kang, Zhanting; Li, Zhaoyi; Tian, Jiaqi; Zhou, Hongyan; Su, Wei; Zhong, Jiateng (Frontiers in Immunology, 2025)
Colorectal cancer (CRC) is one of the most prevalent and deadly malignancies worldwide. Recently, ferroptosis, a novel form of regulated cell death characterized by iron dependency and lipid peroxidation, has garnered significant attention from researchers. The mechanisms underlying ferroptosis, including intracellular iron levels, lipid peroxidation, and antioxidant system regulation, offer new insights into cancer treatment strategies. This study aims to explore the emerging role of ferroptosis in the context of immunotherapy for CRC, highlighting its potential mechanisms and clinical applications. We employed a comprehensive review of current literature to elucidate the biological mechanisms of ferroptosis, its relationship with CRC, and the interplay between ferroptosis and immunotherapy. Ferroptosis reshapes the tumor microenvironment (TME) by regulating intracellular iron levels, lipid metabolism, and antioxidant systems, significantly enhancing the efficacy of immune checkpoint inhibitors (ICIs). Meanwhile, traditional Chinese medicine therapies promote antitumor immunity by modulating the TME and inducing ferroptosis. Additionally, advances in nanotechnology have facilitated precise therapy by enabling targeted delivery of ferroptosis inducers or immunomodulators, transforming “cold” tumors into “hot” tumors and further boosting ICI efficacy. This study comprehensively reviews the latest developments in ferroptosis, immunotherapy, traditional Chinese medicine, and nanotechnology in CRC, highlighting the importance of ferroptosis-related biomarkers and novel inducers for personalized treatment. In summary, ferroptosis offers a promising strategy to overcome CRC therapy resistance and enhance immunotherapy efficacy, warranting further investigation and translational application.